Atributos químicos do solo e rendimento de cultivos em experimento de longa duração cultivado com níveis de calcário e de cama de aviário aplicados em superfície - Moura, Cassiano Melo de (2022)
Limestone and poultry litter are widely used in Brazilian agriculture, especially in Paraná, as they are products that have a potential corrective effect on soil acidity. The objective is to evaluate the changes in soil chemical attributes and oat DM production and the yield components and productivity of maize crops due to an application of limestone and successive applications of poultry litter in different doses. A field experiment was carried out in the experimental area of the Universidade Tecnológica Federal do Paraná (UTFPR), Pato Branco campus/PR. The experimental design used was randomized blocks in split plots and four replicates. The main plots corresponded to four doses of limestone, as follows: 0, 2, 4, and 8 t ha-1, applied only once in 2015. In the subplots, the poultry litter was used annually, since 2011, before the winter crop, in the following doses: 0, 4, 8, and 12 t ha-1 (wet basis). The 2020/21 harvest was evaluated with oat (winter)/maize (summer) crops. Soil samples were collected in the 0-20 cm depth layer at the end of the oat cycle. As the doses of limestone and poultry litter increased, there was a significant increase in soil pH, calcium, base saturation, and the sum of bases, in addition to reducing aluminum. The CEC and the contents of organic matter, phosphorus, and potassium increased linearly with poultry litter, not influenced by limestone. Magnesium had an isolated effect on both factors, with linear increases for both. Even without lime application, the maximum dose of poultry litter (12 t ha-1) promoted the highest production of dry oat mass. The poultry litter affected several yield parameters and the maize grain yield, demonstrating its residual effect. Grain yield ranged from 11460 to 13042 kg ha-1 without applying 12 t ha-1 of poultry litter. It was concluded that poultry litter has a high fertilizing potential, but when used with limestone, it can alkalinize the soil. Under the conditions of the study, the poultry litter promoted a high yield of maize and could be an alternative to mineral fertilizer.